Ohrana prav čeloveka v pravovoj sisteme Ukrainy - Zołotar, Olha (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The aim of the article is to present the institutions and legal procedures protecting human and civil rights and liberties in Ukraine. The author also points to the most frequent grounds for submission of applications by Ukrainian nationals to the European Court of Human Rights. She raises questions concerning the actual situation of human rights protection in Ukraine, especially in the context of the armed conflict in eastern Ukraine, during which there have been cases of torture, arbitrary arrest and detention, execution without trial, forced labour and sexual violence as well as destruction and illegal seizure of property.
Keywords: rights and liberties; protection of human rights; the legal system of Ukraine